Bibliotherapy Services in Public Libraries: the Case of Lithuania - Girčienė, Jurgita; Damijonaitytė, Miglė (Knygotyra, 2023)
Bibliotherapy, as an interdisciplinary field, is undeniably heavily researched on a global scale, yet there are relatively few studies, especially empirical ones, devoted exclusively to the problems of public libraries, while those that would focus only on the services provided by librarians themselves, excluding cooperation with specialists in the field of health promotion, have been undetected at all. The concept, typology, methodology of bibliotherapy and specialists, who can provide services in this field, especially the scope of librarians’ possibilities, are still being discussed in multidirectional works of bibliotherapy. The article presents the results of a quantitative empirical study based on the synthesis of multidisciplinary bibliotherapy research, which allowed to determine the librarians’ own possibilities to provide bibliotherapy services, revealing the state of bibliotherapy services provision in Lithuanian public libraries in 2022. In addition, the article provides a comparative analysis of this study and secondary sources, which showed the evolution and development possibilities of the provision of bibliotherapy services in Lithuanian public libraries. It was found that in most libraries, at least one bibliotherapy service is provided by their own staff. Out of them, slightly more than twice (both qualitatively and quantitatively) of services are attributable to passive bibliotherapy, exclusively covering an intrapersonal level of communication, based on recommendations of books to be read, which is traditionally more characteristic of these institutions, rather than those to be associated with its active variety, which includes an individual interaction of a reader with a librarian inspired by the read book, or a group one - with the members of the book club led by them that integrates an interpersonal level of communication as well. However, as shown by the comparative analysis of the results of the quantitative research of the same object of 2022 and 2011, the active bibliotherapy, which promotes the interaction of readers, is also becoming popular in Lithuania as the functions of libraries expand in the direction of socialization. This is largely in line with global trends. Summarizing the data of the latest research presented in the article and previous secondary sources, it can be stated that in the early 21st century, library bibliotherapy began to be developed at the formal level, and after the development breakthrough recorded at the turn of the first and second decades it has already established itself as a service provided by Lithuanian public libraries. The librarians’ attitudes towards it are positive, the motivation to expand the range or scope of bibliotherapy services is increasing. Although librarians both independently and institutionally, usually through projects or occasional trainings deepen their knowledge in this field, yet its lack is still mentioned, and in particular, the lack of practical skills necessary for organizing more formal active bibliotherapy activities, which leads to a lack of confidence in their own abilities and induces them to limit themselves to the role of an event organizer with a guest lecturer. As one of the ways to solve this problem, long-term institutionalized training in bibliotherapy is mentioned. It is available to those who want to improve in this field and to expand library bibliotherapy services, which help to implement the traditional functions of book repositories and reading promotion and more advanced, globally relevant functions of community gathering and reader education.